2019
DOI: 10.12962/j20882033.v30i3.5409
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Scavenging Activity of Chromolaena odorata L. Leaves

Abstract: Chromolaena odorata is one of the plants used by the community as traditional medicine. Some of community in Ambon, Indonesia used C. odorata leaves as wound medicine. This study aims to evaluate free radical scavenging activity from fraction of methanol extract of C. odorata. Methanol extract of C. odorata leaves is known have good free radical scavenging activity. The fractionation from methanol extract of the C. odorata leaves obtained A-E fraction, where fractions C, D and E showed inhibitory activity aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…The assessment of the free radical scavenging strength of C. odorata used the DPPH method. This antioxidant property is assessed based on the electron transfer, which gives a violet solution in ethanol (Maulida et al, 2019). Free radicals are stable at room temperature, reduced in antioxidant molecules, resulting in a colorless ethanol solution.…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of the free radical scavenging strength of C. odorata used the DPPH method. This antioxidant property is assessed based on the electron transfer, which gives a violet solution in ethanol (Maulida et al, 2019). Free radicals are stable at room temperature, reduced in antioxidant molecules, resulting in a colorless ethanol solution.…”
Section: Resultsmentioning
confidence: 99%
“…Chromolaena odorata is one of the plants used by the community as traditional medicine. Some of community in Ambon, Indonesia used Chromolaena odorata leaves as wound medicine due to the free radical scavenging activity from fraction of methanol extract of the plant (Maulida et al, 2019). In an earlier study, the free radical scavenging and antioxidant activity of the leaves of Chromolaena odorata was evaluated and the researchers reported that the ethanol and methanol extracts reveal significant antioxidant properties (Bhargava et al, 2013).…”
Section: Antioxidant Property Of Chromolaena Odoratamentioning
confidence: 99%
“…Menurut Vital & Rivera, (2009) menyatakan bahwa daun kirinyuh (Chromolaena odorata L.) mengandung senyawa metabolit sekunder seperti tannin, fenol, flavanoid, saponin, steroid dan minyak essensial. Maulida, Putri, & Fatmawati, (2019) juga menyatakan bahwa pada daun Chromolaena odorata L. mengandung beberapa senyawa kimia salah satunya flavonoid. Menurut Robinson, (1995); Vital & Rivera, (2009) bahwa flavonoid, quersetin dan kaempferol merupakan kandungan senyawa aktif yang berperan sebagai antiinflamasi.…”
Section: ) Penyimpanan Darah Tikusunclassified